2020
DOI: 10.3390/molecules25112537
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic (E)-3-Phenyl-5-(phenylamino)-2-styryl-1,3,4-thiadiazol-3-ium Chloride Derivatives as Promising Chemotherapy Agents on Cell Lines Infected with HTLV-1

Abstract: Synthesis of four compounds belonging to mesoionic class, (E)-3-phenyl-5-(phenylamino)-2-styryl-1,3,4-thiadiazol-3-ium chloride derivatives (5a–d) and their biological evaluation against MT2 and C92 cell lines infected with human T-cell lymphotropic virus type-1 (HTLV-1), which causes adult T-cell leukemia/lymphoma (ATLL), and non-infected cell lines (Jurkat) are reported. The compounds were obtained by convergent synthesis under microwave irradiation and the cytotoxicity was evaluated using 3-(4,5-dimethylthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…On the other hand, for HSA, there are three main binding pockets for both endogenous and exogenous compounds: subdomain IIA (site I) located in a hydrophobic binding pocket, subdomain IIIA (site II), also located in a hydrophobic binding pocket, and subdomain IB (site III) located on the surface of the albumin. 48,71,72 All binding sites are able to accommodate the vanadium( v ) complexes, however, site III is the main pocket according to the molecular docking score values (Table 4). Reported in silico data indicated site I or site III as the main binding pockets for the interaction between HSA and some V V -complexes derived from pyridoxal or salicylaldehyde, 31,57 suggesting a dependence on the nature of the ligands in the interactive profile with albumin.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, for HSA, there are three main binding pockets for both endogenous and exogenous compounds: subdomain IIA (site I) located in a hydrophobic binding pocket, subdomain IIIA (site II), also located in a hydrophobic binding pocket, and subdomain IB (site III) located on the surface of the albumin. 48,71,72 All binding sites are able to accommodate the vanadium( v ) complexes, however, site III is the main pocket according to the molecular docking score values (Table 4). Reported in silico data indicated site I or site III as the main binding pockets for the interaction between HSA and some V V -complexes derived from pyridoxal or salicylaldehyde, 31,57 suggesting a dependence on the nature of the ligands in the interactive profile with albumin.…”
Section: Resultsmentioning
confidence: 99%
“…One of the compounds induced necrosis after 24 h in Jurkat and MT-2 cell lines. The experimental (fluorimetric method) and theoretical (molecular docking) results suggested that the mechanism of action could be related to its capacity to intercalate into DNA, and they presented spontaneous and moderate interaction with albumin in human serum albumin (HSA)-binding affinity assay by multiple spectroscopic techniques (circular dichroism, steady-state and time-resolved fluorescence), zeta potential, and molecular docking calculations, indicating good biodistribution in the human bloodstream (Table 1) [23].…”
Section: New Studies About Drugs To Treat Htlv-1 Infectionmentioning
confidence: 99%
“…The compounds with electron donor substituents (R=CH3 or OCH3) were more active, showing cell death by necrosis, interacting with DNA, and exhibiting lower hydrophobicity. Also, the preliminary pharmacokinetic profile obtained through human serum albumin (HSA) binding affinity using multiple spectroscopic techniques, zeta potential, and molecular docking calculations revealed that all the mesoionic compounds presented good binding parameters toward serum albumin, indicating feasible biodistribution in the human bloodstream (Table 2) [23].…”
Section: Updates In Drug Research For the Treatment Of Adult T-cell L...mentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds are of particular interest as biologically active compounds [2]. Among the derivatives of 1,3,4-thiadiazole are substances with antitumor [3][4][5][6][7][8][9][10][11], antiviral [11][12][13][14][15][16][17], antimicrobial [10,[18][19][20][21][22][23][24][25][26][27][28][29][30], antioxidant [29,30], neuroprotective [31], antiprotozoal [32], and anti-inflammatory [33,34] activity. In addition, these substances act as inhibitors of acetylcholinesterase [35,36], αglucosidase [37], and carbonic anhydrase [38].…”
Section: Introductionmentioning
confidence: 99%